The 4th NextGen therapies for SJIA and MAS: part 2 phenotypes of refractory SJIA and the landscape for clinical trials in refractory SJIA - Grant Schulert; Sebastiaan J. Vastert; Alexei A. Grom (BMC, 2024)
Abstract Although the introduction of the IL-1 and IL-6 inhibiting biologics in 2012 has revolutionized the treatment and markedly improved outcomes for many patients with SJIA, about 20% of these patients continue to have active disease, have markedly decreased quality of life and high disease activity as well as treatment-related morbidity and mortality. There is a clear need to define these disease states, and then use these definitions as the basis for further studies into the prevalence, clinical features, and pathophysiologic mechanisms. While such patients are most likely to benefit from novel therapies, they are very difficult to enroll in the ongoing clinical trials given the unique features of their disease and large numbers of background medications. The discussions at the NextGen 2022 conference focused on strategies to overcome these obstacles and accelerate studies in refractory SJIA.